THE ROLE OF THE VILLAGE GOVERNMENT IN IMPROVING COMMUNITY WELFARE THROUGH EMPOWERING SEAWEED CULTIVATION IN LASITAE VILLAGE, TANETE RILAU DISTRICT, BARRU REGENCY - Lukman , Sri Hardiyanti; Aminah , A. (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal